EVALUASI PEMERIKSAAN X-RAY PENUMPANG DAN BARANG DI BANDARA DENGAN SIMULASI (STUDI KASUS BANDARA ADISUTJIPTO âYOGYAKARTA) - , HARRY YANTO LUMBAN BATU ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The increasing growth of passengers of air transportation should be balanced with the increasing rate of airport safety according to the Government Regulation No. 3 year of 2001 on Aviation Safety and Security, where people and goods must be examined for safety. The evaluation of X-Ray examination service is done to observe the service performance which refers to SKEP/284/ X/1999 with maximum time of X-Ray service will be 3 minutes for normal condition and 8 minutes for special condition. This research is done to determine the variables of the X-Ray evaluation such as time of passengers arrival, time of service, and end of service time. The data field is analyzed by grouping the distribution of event frequencies and it is then generated by using random distribution of each event. The result of the simulation will be examined with the data field to find the correlation between the simulation model and the real event. The result of the simulation with the standardized normal time for X-Ray examination will effect the delayed in time service due to the demand of the service is bigger than the ability of the service performance. Thus, optimalization of the service should be done by increasing the queuing capacity and X-Ray examiner. It can be concluded that the evaluation of X-Ray examination with simulation can be used as a mean of decision making in maximizing and increasing the X-Ray examination service for passengers and goods at the airport